2009
DOI: 10.1016/j.ccr.2009.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Androgen Receptor Transcriptional Activity and Specificity by RNF6-Induced Ubiquitination

Abstract: Summary The androgen receptor (AR) plays a critical role in prostate cancer. We have identified an ubiquitin E3 ligase RNF6 as one of AR-associated proteins in a proteomic screen. RNF6 induces AR ubiquitination and promotes AR transcriptional activity. Specific knockdown of RNF6 or mutation of RNF6-induced ubiquitination acceptor sites on AR selectively alters expression of a subset of AR target genes and diminishes recruitment of AR and its coactivators to androgen-responsive elements present in the regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
252
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(266 citation statements)
references
References 53 publications
(61 reference statements)
13
252
1
Order By: Relevance
“…Mdm2 leads to AR polyubiquitination and subsequent degradation, 22 whereas RNF6 mediates an atypical ubiquitination chain on AR, thus enhancing its transcriptional activity. 23 In the present study, we identified that HERC4 specifically mediates c-Maf ubiquitination but has no effect on MafA and MafB protein degradation, suggesting that HERC4 can differentiate its substrate although c-Maf shares a very high similarity with MafA and MafB. Moreover, in a panel of HECT-E3 ligases, HERC4 is the only one to mediate c-Maf degradation, further demonstrating that HERC4 specifically identifies c-Maf and mediates its ubiquitination and degradation, although other E3 ligases not in the examined panel will also mediate c-Maf ubiquitination (such as HUWE1 which was found in the c-Maf IP complexes), the current study at least suggests c-Maf stability and function is strictly regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Mdm2 leads to AR polyubiquitination and subsequent degradation, 22 whereas RNF6 mediates an atypical ubiquitination chain on AR, thus enhancing its transcriptional activity. 23 In the present study, we identified that HERC4 specifically mediates c-Maf ubiquitination but has no effect on MafA and MafB protein degradation, suggesting that HERC4 can differentiate its substrate although c-Maf shares a very high similarity with MafA and MafB. Moreover, in a panel of HECT-E3 ligases, HERC4 is the only one to mediate c-Maf degradation, further demonstrating that HERC4 specifically identifies c-Maf and mediates its ubiquitination and degradation, although other E3 ligases not in the examined panel will also mediate c-Maf ubiquitination (such as HUWE1 which was found in the c-Maf IP complexes), the current study at least suggests c-Maf stability and function is strictly regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicated that RNF6 mediates the polyubiquitination of LIM domain kinase 1 (LIMK1) via Lys-48 and targets it for proteasomal degradation. Additionally, RNF6 promoted AR transcriptional activity by inducing androgen receptor (AR) ubiquitination (16,17). Polyubiquitin chain formation proceeds typically via isopeptide bond formation between the G76 carboxyl group of the 'n+1' ubiquitin to the ε-amino group of a lysine within the preceding ubiquitin.…”
Section: Discussionmentioning
confidence: 99%
“…IPs were carried out by adding ϳ1 l of antibody per ml cell lysates and allowing incubation for ϳ16 h at 4°C. For detecting ubiquitinated proteins, denaturing conditions were used prior to IP (52). For Western blot analyses, cell lysates were separated on 8 -10% SDS-polyacrylamide gels.…”
Section: Methodsmentioning
confidence: 99%
“…All mutations were confirmed by sequencing. Expression constructs for FLAG-tagged AR, HA-RNF6, Probasin luciferase reporter ARR2-Luc, and specific shRNA constructs were described previously (17,51,52).…”
Section: Methodsmentioning
confidence: 99%